Tri Kaya Parisudha's Image-Oriented Story Media to Increase The Interest in Reading of Three Grade Elementary School Students - Adnyana, I Ketut Suar; Dewa Ayu Made Manu Okta Priantini; Ni Made Suarningsih (Universitas Pendidikan Ganesha, 2023)
Lack of media literacy so that students are less interested in reading. It has an impact on students' understanding that needs to be improved. This study aimed to develop a Tri Kaya Parisudha Oriented Picture Story Book to increase reading interest in third-grade elementary school students. This research is a research and development (research and development). The subjects of the research trials were class III students. Methods of data collection using a questionnaire. The data collection instrument used was an evaluation sheet (questionnaire). Data analysis used descriptive qualitative and quantitative descriptive analysis. The results of the evaluation of this e-module product are based on six aspects, namely: content aspect of the field of study / with a percentage of the achievement level of 87.00% with a proper predicate. Judging from the aspect of learning design with an achievement percentage of 87.50% (feasible). Aspects of learning media with a percentage of the achievement level of 90.60% predicate very good / very decent. Aspects of the trial, small group trials, with a percentage of achievement rate of 93.70%, the title is very feasible. Aspects of field trials with a percentage level of achievement of 94.50% predicate are feasible. Thus the product in the form of a picture storybook oriented towards Tri Kaya Parisudha has a good level of validity and is suitable for use in the learning and literacy process.